The Analysis of Maxim Violation in Generation Z Conversation on WhatsApp - Akyuni, Siti Nur; Aisyah, Siti; Andayani , Endah Alamsari (Center of Language and Cultural Studies [CLCS], 2024)
A good conversation is one that has rules. According to Grace's theory (1975), there are four rules of conversation, namely, the maxim of quantity, the maxim of quality, the maxim of relation, and the maxim of manner. In fact, Generation Z often ignores these rules when having conversations. The purpose of this research is to find out the types of maxims violated by Generation Z on WhatsApp. This study used qualitative research methods. The selected participants were Generation Z, namely five students of the English Education Department class of 2020 C. The reason for selecting these participants was because, currently, the majority of Generation Z is at the tertiary level. Document analysis and content analysis were used as data collection techniques. Condensing, presenting the data, and drawing conclusions are all parts of the data analysis process. The result is that the majority of Generation Z violates all types of maxims, and the most dominant is the maxim of relation. In conclusion, even though Generation Z has learned the rules of conversation, the fact is that in carrying out conversations, Generation Z does not apply the existing rules, so conversations become ineffective.